Effect Of Perceived Behavior ControlAnd Machiavellian Nature Of Fraud PreventionWith Whistleblowing As InterveningVariable - Riyanto Dwi Nugroho; Andi - Kartika (International Journal of Artificial Intelligence Research, 2022)
PT. Cakrawana Furnindo Utama is facing a problem phenomenon, where acts of fraud occur in almost all management lines. This condition occurs because the management of the company itself has not carried out strict and integrated supervision of employees in carrying out their operational activities. This indicates that fraud prevention by companies is still low and needs to be improved. The research objective is to determine the impact of perceived behavior control and Machiavellian behavior partially on whistleblowing and fraud prevention, the impact of whistleblowing on fraud prevention and the role of whistleblowing in mediating the impact of perceived behavior control on fraud prevention and the impact of Machiavellian behavior on fraud prevention. The population and at the same time as the sample are all employees of PT. Cakrawana Furnindo Utama numbered 100 people, using the census method. The data analysis technique is a stepwise linear regression test (Two Stage Least Square). From the results of data analysis, it is known that perceived behavior control and Machiavellian traits partially have a positive and significant impact on whistleblowing, perceived behavior control has no impact on fraud prevention, while Machiavellian traits have a positive and significant impact on fraud prevention, on the other hand whistleblowing has a positive and significant impact on prevention of fraud, whistleblowing does not mediate the impact of perceived behavior control on fraud prevention and whistleblowing does not mediate the impact of Machiavellian traits on fraud prevention.